Antibiotic Resistance of MRSA in the Russian Federation - V. V. Gostev; O. S. Kalinogorskaya; L. N. Popenko; T. V. Chernenkaya; Z. S. Naumenko; T. M. Voroshilova; YU. A. Zakharova; O. E. Khokhlova; A. N. Kruglov; M. G. Ershova; I. V. Molchanova; S. V. Sidorenko (Антибиотики и Химиотерапия, 2020)
The results of the multicentre trial on estimation of MRSA antibiotic susceptibility to 17 antibiotics are presented. 474 nonrepeting isolates of MRSA (mecA+), collected in 2011-2014 in 10 cities of the Russian Federation were used in the trial. The antibiotic susceptibility was determined by the method of serial microdilutions in broth with estimation of the MICs in accordance with the international standards CLSI 2014 and EUCAST 2014. The highest levels of the MRSA resistance were stated against ciprofloxacin - 92% (MIC50 32 mcg/ml), gentamicin - 85% (MIC50 128 mcg/ml), erythromycin - 54% (MIC50 32 mcg/ml) and clindamycin - 45% (MIC50 0.03 mcg/ml), as well as against rifampicin - 38% (MIC50 0,06 mcg/ml). The frequency of MRSA isolated at the vancomycin dose of 2 mcg/ml equaled 26%. No correlation of the decrease in susceptibility to vancomycin and rifampicin was observed. In 5% of MRSA isolated from infected surgical wounds in patients with bone infection or sepsis, there was observed a decrease in the susceptibility to ceftarolin (MIC 2-4 mcg/ml). Co-trimoxasole, I'usidic acid (MIC50 0.06 mcg/ml) and mupirocin (MIC50 0.5 mcg/ml) showed high antibacterial activity, 93-98% of the isolates being susceptible to the drugs. No resistance to linezolid and tigecycline was detected. By the associate resistance spectrum, most of the MRSA isolates were characterized by resistance to drugs of 3-7 groups (56%). The phenotypes with simultaneous resistance to drugs of 8-10 groups amounted to 6%. As a whole, 70 variants of associate resistance combinations were detected.